8(t-3)+4t=4(3t+4)-12

Simple and best practice solution for 8(t-3)+4t=4(3t+4)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(t-3)+4t=4(3t+4)-12 equation:


Simplifying
8(t + -3) + 4t = 4(3t + 4) + -12

Reorder the terms:
8(-3 + t) + 4t = 4(3t + 4) + -12
(-3 * 8 + t * 8) + 4t = 4(3t + 4) + -12
(-24 + 8t) + 4t = 4(3t + 4) + -12

Combine like terms: 8t + 4t = 12t
-24 + 12t = 4(3t + 4) + -12

Reorder the terms:
-24 + 12t = 4(4 + 3t) + -12
-24 + 12t = (4 * 4 + 3t * 4) + -12
-24 + 12t = (16 + 12t) + -12

Reorder the terms:
-24 + 12t = 16 + -12 + 12t

Combine like terms: 16 + -12 = 4
-24 + 12t = 4 + 12t

Add '-12t' to each side of the equation.
-24 + 12t + -12t = 4 + 12t + -12t

Combine like terms: 12t + -12t = 0
-24 + 0 = 4 + 12t + -12t
-24 = 4 + 12t + -12t

Combine like terms: 12t + -12t = 0
-24 = 4 + 0
-24 = 4

Solving
-24 = 4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 11x-14=13x | | 0.25(3x-8)=2(0.5x+4) | | 6.4i+9.21=50.7 | | -4k-7+5= | | 3+1/2c=3/4c-5 | | 7-y=20 | | (8-w)(4w-2)=0 | | 10x-8=6x^2 | | 5x+35=2x+80 | | 14x=10+10 | | -(7y+2)-(6y-4)=-2 | | (x-3)/x^2 | | 16+32+x=72 | | 2x+71=4x+51 | | 4x+9y=106 | | (x+2.8)(37.2-2x)=50 | | 3x(3)-78=144 | | 6x-15=4x+13 | | (a-1)(a-5)=0 | | 8t^2-5t-25=0 | | 4n+12+n=-3n+17 | | 8.2x+1.5=21.5-1.8x | | 2t^2-6t+18=0 | | 5-8x+7=-9x-9-5 | | 2b/5-1/0=-1/2 | | x^2+30x+117=0 | | x-8.9=-4.7 | | 10b^2-18b-36=0 | | 15p+p=7-12 | | p+39=14 | | ln(5x+4)=5 | | 5(k-8)-2(k-1)=2k-9 |

Equations solver categories